2021
DOI: 10.3390/jpm11121325
|View full text |Cite
|
Sign up to set email alerts
|

Escalation Time to Open Triple Combination Therapy from the Initiation of LAMA versus ICS/LABA in COPD Management: Findings from Comparing the Incidence of Tiotropium and ICS/LABA in Real-World Use in South Korea (CITRUS) Study

Abstract: Background: bronchodilators are the key treatment for chronic obstructive pulmonary disease (COPD), however, inhaled corticosteroids (ICSs)/long-acting β2-agonists (LABA) are widely prescribed. We compared the escalation time to open triple combination therapy between long-acting muscarinic receptor antagonists (LAMA) and ICS/LABA in COPD management. Methods: this retrospective study included COPD patients selected from the National Health Insurance Service of South Korea from January 2005 to April 2015. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Our real-world findings of reduced medical costs in the LAMA compared to the LABA/ICS treatment group provided more rationale for using LAMA bronchodilators over LABA/ICS combination as an initial treatment for the patients with low risk of exacerbation, showing the reduced medical cost directly and the increased adherence indirectly, in addition to the delayed escalation to triple therapy. 17 The findings of our study also provide another aspect, medical costs, to the recent changes in the GOLD 2023 update, in which the role of LABA/ICS in COPD is much diminished and the addition of ICS at treatment initiation is only suggested as a component of triple therapy for GOLD risk group E. 1 Furthermore, although other recent real-world comparative studies showed that LABA/ICS was as effective as LAMA or LAMA/LABA combination in preventing exacerbation, in the same studies LABA/ICS was associated with pneumonia more than LAMA or LAMA/LABA. 16 , 26 Therefore, our study adds financial insight to the recent recommendation in which the use of ICS should be limited to patients with a high risk of exacerbation, preferably as a component of triple therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our real-world findings of reduced medical costs in the LAMA compared to the LABA/ICS treatment group provided more rationale for using LAMA bronchodilators over LABA/ICS combination as an initial treatment for the patients with low risk of exacerbation, showing the reduced medical cost directly and the increased adherence indirectly, in addition to the delayed escalation to triple therapy. 17 The findings of our study also provide another aspect, medical costs, to the recent changes in the GOLD 2023 update, in which the role of LABA/ICS in COPD is much diminished and the addition of ICS at treatment initiation is only suggested as a component of triple therapy for GOLD risk group E. 1 Furthermore, although other recent real-world comparative studies showed that LABA/ICS was as effective as LAMA or LAMA/LABA combination in preventing exacerbation, in the same studies LABA/ICS was associated with pneumonia more than LAMA or LAMA/LABA. 16 , 26 Therefore, our study adds financial insight to the recent recommendation in which the use of ICS should be limited to patients with a high risk of exacerbation, preferably as a component of triple therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This study was a retrospective, non-interventional cohort study using a national health insurance claims database from the National Health Insurance Service (NHIS) from South Korea. 17 The NHIS data provides demographic characteristics and healthcare information of COPD patients, including comorbidities and medical treatment. The study period was from January 1, 2002 through April 30, 2016, consisting of the baseline period of 36 months and the patient enrollment period of 124 months (January 1, 2005 to April 30, 2015).…”
Section: Methodsmentioning
confidence: 99%